The Effect of Layer Thickness and Nozzle Diameter in Fused Deposition Modelling Printing on the Flexural Strength of Zirconia Ceramic Samples Produced by a Multistage Manufacturing Process - Anton Smirnov; Oleg Yanushevich; Natella Krikheli; Yulia Zhukovskaya; Mihail Soloninkin; Petr Naumenko; Nestor Washington Solis Pinargote; Pavel Peretyagin; Sergey Grigoriev; Nikita Nikitin (Ceramics)
The process of creating ceramic items using fused deposition modelling (FDM) enables the creation of intricate shapes for a variety of purposes, including tooling and prototyping. However, due to the numerous variables involved in the process, it is challenging to discern the impact of each parameter on the final characteristics of FDM components, which impedes the advancement of this technology. This paper deals with the application of statistical analysis in the study of the dependence of the flexural strength of sintered zirconia disks on the printing parameters (nozzle diameter, layer thickness, and infill pattern) of the fused deposition method printing of a ceramic–polymer filament containing 80 wt.% zirconia and 20 wt.% polylactide. X-ray-computed tomography and diffraction systems, scanning electron microscopy combined with energy-dispersive spectroscopy, were used for a microstructural analysis of the sintered samples. It was found that the nozzle diameter and infill pattern have no significant influence on the flexural strength values. It was assumed that this is due to the heterogeneous distribution of the ceramic phase in the manufactured filament during extrusion. On the other hand, correlation analysis and analysis of correlation diagrams have shown that the thickness of the filling layer has the greatest effect on flexural strength. The maximum (684 MPa) strength value was found in a sample printed with a layer thickness of 0.2 mm. The minimum layer thickness ensures a more uniform distribution of ceramic particles and minimizes defects in samples that occur during FDM printing. The results obtained make it possible to optimize the considered process of manufacturing ceramic products from ZrO2 printed using FDM technology from extruded composite filaments.